Somatic meiosis and development of the juvenile gametophyte in members of the Batrachospermales sensu lato (Rhodophyta) - Necchi Jr., Orlando [UNESP]; Carmona Jiménez, Javier [UNESP] (Taylor & Francis, 2002)
Seven populations (six in culture and one sampled directly from nature) of the freshwater red algal families Batrachospermaceae, Lemaneaceae and Thoreaceae were examined, involving three species of Batrachospermum, two of Paralemanea and one of Thorea. All 'Chantransia' stages ultimately produced juvenile gametophytes. The production of juvenile gametophytes in the three populations of Batrachospermum was generally most abundant at 15°C and low irradiances (47-68 μmol photons m-2 s-1). The most abundant gametophyte development in the Paralemanea species was observed at 10°C and low or high irradiances (47-142 μmol photons m-2 s-1). Gametophyte production in Thoreaceae occurred at higher temperatures (20°C) and also at low irradiances. In species of the Batrachospermaceae and Lemaneaceae, the 'elimination cells' can be situated on the basal or suprabasal cell of the juvenile gametophyte, but the position is usually fixed in individual species. The presence and position of the elimination cells remain to be established in Thoreaceae. Our results corroborate a previous study suggesting that the position of elimination cells is such a constant feature that it is of potential diagnostic value at the generic or infrageneric (sectional or specific) level. The characteristics observed in the development of the juvenile gametophytes in species of Batrachospermaceae and Lemaneaceae essentially agreed with general descriptions in the previous studies. The characteristics of the Thoreaceae, with a distinctive developmental pattern of the juvenile gametophyte and the occurrence of two morphological types in the 'Chantransia' stage, support the proposal to elevate it to the ordinal level. Two remarkable observations in Batrachospermum species were the production of numerous juvenile gametophytes from filaments of the same plant of the 'Chantransia' stage and the formation of a system of rhizoidal filaments or cell agglomeration of the juvenile gametophytes, which produced new gametophytes. These two characteristics potentially increase the formation of additional gametophytes under favourable conditions.
Keywords: Batrachospermum; Paralemanea; Thorea